THE ROLE OF SOCIAL MEDIA IN PUBLIC DECISION-MAKING PROCESSES AND COMMUNITY PARTICIPATION - Syarifuddin; Indah Sulistiani; Bikah Kusti Noviani; Al-Amin; Rahma Helal Al_ Jbour (Adisam Publisher, 2026)
Social media plays an important role in increasing public participation. Platforms such as Twitter, Facebook and Instagram enable the rapid and widespread dissemination of information among the public, so that people become more informed about important issues. In addition, social media provides a space for people to express their opinions and interact directly with policymakers, creating a more inclusive and democratic form of participation. Through social media, individuals are able to engage in public discussions, contribute to social movements, and influence societal decision-making processes. However, the positive impact of social media on public participation must also be managed wisely due to significant challenges. The spread of inaccurate news and misinformation through social media can cause confusion and conflict in society. Algorithms that favor controversial or extreme content also have the potential to exacerbate political polarization and divide communities. To face these challenges, good digital literacy is needed so that people can be more critical in evaluating the information they receive and share. In addition, collaboration between the government, social media platform administrators and the public is needed to ensure that social media can be utilized positively and constructively to increase public participation. With the right approach, social media has the potential to be an effective tool to create a more inclusive, transparent and responsive public decision-making process.